Eksplorasi Faktor Yang Mempengaruhi Program Gerakan Mentawai Anti Stunting Gizi Buruk Peduli Anak (Masgiburdua) Di Kabupaten Kepulauan Mentawai - Nide, Erick Maulana Putra; Yusran, Rahmadani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aims to explore the Mentawai Anti-Stunting Malnutrition Caring for Children (MASGIBURDUA) movement program in the Mentawai Islands District. Based on Regent Regulation (Perbup) Number 7 of 2020 this program aims to integrate the implementation of programs and activities to accelerate the reduction of stunting. In this movement it becomes a collaborative collaboration between the central government, health and society. The main targets of the movement in this program are pregnant women, nursing mothers and children under the age of 6 months, breastfeeding mothers and children aged 7 to 23 months. The method in this research is descriptive qualitative, the focus is on the offices and agencies involved in stunting prevention and at the same time being research informants. The results of this study indicate that the Government of the Mentawai Islands Regency implements stunting prevention by implementing the masiburdua program in several forms of activity, namely providing education and improving the nutritional status of the community and the quality of resources such as improving community nutrition, establishing diet improvement posts, regular monitoring of toddlers. implementation is constrained due to several factors such as limited availability of budget and infrastructure, inadequate access to transportation due to the considerable distance, lack of public understanding due to lack of outreach and education to the public about the importance of stunting prevention.